PENGARUH ENVIRONMENTAL, SOCIAL AND GOVERNANCE DAN PROFITABILITAS TERHADAP HARGA SAHAM PERUSAHAAN - Elisha Luchianna; Hexana Sri Lastanti (STMIK Widuri Jakarta, 2025)
The focus on this research is on factors that can influence the stock prices of companies. The objective is to determine whether there is a relationship between the variables of environmental, social and governance and profitability on stock price. The data on this study were obtained using secondary data from the annual and sustainability report of the energy sector lusted on the Indonesia Stock Exchange (IDX) for the period 2021 - 2023. This study sampled 126 companies unbalanced data panel that meets the criteriaby purposive sampling. The study employs data regression analysis using SPSS 25.0. The results of this study indicate that environmental, social and governance have a positive impact on the stock price companies, profitability is proxied by ROA and NPM have a positive impact on the stock price companies, while profitability is proxied by ROE have no effect the stock price.